Effectiveness of mindfulness-based interventions on burnout, resilience and sleep quality among nurses: a systematic review and meta-analysis of randomized controlled trials - Jin, Dou; Yujia, Lian; Lili, Lin; Asmuri, Siti Noraini; Peixi, Wang; Rajen Durai, Ruthpackiavathy (BioMed Central, 2025)
Background: Due to the occupational characteristics of clinical work, nurses often face many challenges related to physical and psychological health. Mindfulness-based interventions are psychological intervention therapies based on mindfulness, which has been proven to effectively improve burnout, resilience and sleep quality among nurses. But there is not sufficient evidence to examine the effectiveness of mindfulness-based interventions on burnout, resilience and sleep quality among nurses. Objective: To evaluate the effectiveness of mindfulness-based interventions in reducing burnout, resilience and sleep quality among nurses and enhance the quality of nursing medical service. Methods: Seven electronic databases, including PubMed, EMBASE, Scopus, Web of Science, PsycINFO, CINAHL and Chinese National Knowledge Infrastructure were searched from their inception to November, 2024. Randomized controlled trials investigated the effects of mindfulness-based interventions for improving burnout, resilience and sleep quality among nurses. The quality of the included studies was assessed by the Cochrane Risk of Bias Tool v2. Meta-analyses were conducted using Review Manager 5.4 and the Grading of Recommendations, Assessment, Development, and Evaluation approach was used to assess the certainty of evidence. Results: A total of 4622 studies were initially retrieved and 16 articles (n = 1384 individuals) were included. The meta-analysis showed that mindfulness-based interventions could effectively improve burnout (SMD = -1.43, 95% CI: -1.94 to − 0.92, P < 0.001), resilience (MD = 9.78, 95% CI: 0.38 to 19.17, P = 0.04) and sleep quality (SMD = -1.1, 95% CI: -1.79 to -0.41, P = 0.002). However, due to some moderate risk of bias and high level of heterogeneity, the overall quality of the evidence was not high. Conclusion: Mindfulness-based interventions could improve burnout, resilience and sleep quality among nurses. This suggests that mindfulness-based interventions can provide preliminary clinical practice support for addressing mental health and well-being and work quality of nurses. But because of moderate to low certainty of evidence and some concerns of bias, more rigorous studies are needed to confirm the effectiveness of mindfulness-based interventions for improving the outcomes.